Fravær som et kompositionsprincip i Helle Helles novellesamling Rester (1996) - Cymbrykiewicz, Joanna (Folia Scandinavica Posnaniensia, 2009)
The paper analyses the short story collection titled Remnants written by the notable Danish author, Helle Helle. This work is characteristic of the contemporary minimalist movement, and is one of the most significant works of the 1990’s in Danish literature. The main point of the paper is the notion of absence and loss, which is treated as the work’s dominating principle. The paper attempts to prove that this governing principle of “absence and loss” both applies to the collection’s plot and its composition. Accordingly, several examples from the text are included to demonstrate the principle’s relevance.